Legal Protection Of Consumers Due To Default In Online Buying And Selling Transactions - Raplin Djauhari (Estudiante Law Journal, 2020)
This research aims to find out the legal protection of consumers due to default in online buying and selling transactions and to know the responsibility of business actors due to default in online buying and selling transactions.This research uses a statutory approach with a type of research that is normative legal research.The results showed that (1) Legal protection of consumers due to default in online buying and selling transactions is intended to protect their rights that business actors do not fulfill. The protection of the law against consumers can be measured by how the law protects the rights of the rights of consumers, while the rights of consumers are regulated in the Civil Code Article one thousand two hundred and thirty-five, Article one thousand four hundred seventy-four, Article one thousand four hundred fifty-eight, article one thousand four hundred seventy-four, Article one thousand five hundred and thirteen,  One thousand five hundred and fourteen. Consumer protection law Article forty-five, Article forty-six and Article forty-seven, as well as in the law on information and electronic transactions Article seventeen paragraph two, Article thirty-eight. (2) The responsibility of business actors due to default in online buying and selling transactions is to compensate consumers. Indemnity includes returning money, replacing it according to its value.Keywords: Criminal Acts, Theft, Children